Improvement of platelet in thrombocytopenic HCV patients after treatment with direct-acting antiviral agents and its relation to outcome. (3rd April 2021) - Soliman, Zeinab; El Kassas, Mohamed; Elsharkawy, Aisha; Elbadry, Mohamed; Hamada, Yasser; ElHusseiny, Ramy; M. El-Nahaas, Saeed; Fouad, Rabab; Esmat, Gamal; Abdel Alem, Shereen
Abstract: Little is known about evolution of platelet count after treatment with direct-acting antiviral agents (DAAs). The study aimed to evaluate the changes in platelet count after treatment with DAAs among thrombocytopenic patients with HCV-related advanced fibrosis and cirrhosis. A total of 915 chronic HCV patients with advanced fibrosis and cirrhosis who were treated with different DAAs-based regimens were retrospectively enrolled in final analysis. Included patients were those with thrombocytopenia (TCP). Platelet count was recorded at baseline, end of treatment (EOT) and 24-weeks after EOT (SVR24). Changes in platelet count and its relation to SVR were analyzed. The overall SVR24 rate was 98.8%. The platelet count showed statistically significant improvement from baseline to EOT (107 (84–127) × 10 3 /mm 3 vs. 120 (87–153) × 10 3 /mm 3 ( P = <0.0001) but remained unchanged thereafter to SVR24. Among responders, the platelet count significantly increased at SVR24 compared to baseline ( P = <0.0001) but in relapsers, there was improvement in platelet count that didn't reach statistical significance ( P = 0.9). Logistic regression analysis showed that higher Child-Pugh score and more advanced fibrosis at baseline were significant predictors of decreasing of platelet count and development of severe TCP at SVR24. Among thrombocytopenic patients with HCV-related advanced fibrosis and cirrhosis, the platelet count improved after treatment with DAAs regardless to treatment response.